The Picker house and collection a late 1960s home for art and design - Black, Jonathan 1969- (London Philip Wilson Publishers, an imprint of I.B. Tauris & Co Ltd, 2013)
Picker House is a remarkable late 1960s modernist home specifically designed to accommodate a significant international collection of modern and contemporary painting and sculpture. This book brings together leading researchers in their respective fields who examine in depth every aspect of this unique place
'An entrepreneurial wizard': a biographical sketch of Stanley Picker / Jonathan Black -- The Picker House: a British house with and international outlook / Fiona Fisher -- The Picker House interior / Penny Sparke -- The Picker garden / Rebecca Preston -- The Picker House painting, print and drawing collection / Jonathan Black -- The Picker House sculpture collection / Fran Lloyd -- The Picker House: contemporary perspectives / David Falkner -- Stanley Picker Fellowships: art and design
Includes bibliographical references (pages 190-205) and index
Keywords: Picker, Stanley -- 1913-1982 -- Homes and haunts; Picker House; Architecture, Domestic -- England -- London; Art -- Private collections -- England -- London; Art and architecture -- England -- London